PERAN KIAI DALAM MEMBANGUN PARTISIPASI PEMILIH - Nurhadi Nurhadi; Sunarso Sunarso (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This article aims to discuss the role of kiai in building voter participation. The method used is a qualitative approach. Data collection using observation, interviews, and observations. Analysis uses an interactive model. The results of the study show that scholars have 3 (three) roles in politics, namely as political political patrons, political elites, and political mediators. Kiai as political patrons become a reference in making political choices. Kiai are active political elites in the management of political parties and mass mobilization. Kiai as political mediators mediate in political conflicts.